2020
DOI: 10.5688/ajpe7575
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Advanced Pharmacy Practice Experiences on Residency Interview Invitations

Abstract: Objective. To determine how postgraduate year one (PGY1) pharmacy residency program directors perceive factors related to advanced pharmacy practice experiences (APPEs) when selecting candidates for residency interviews. Methods. An online cross-sectional nationwide survey of 1,280 PGY1 residency program directors was conducted. Participants were asked to rank the overall influence of five APPE categories, including location, structure, elective type, timing, and preceptor references, as well as the desirabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…The authors identified 13 studies meeting inclusion criteria related to the objective of this scoping review (Figure 1) and are described in Tables 1-3. [13][14][15][16][17][18][19][20][21][22][23][24][25] The studies were grouped into three categories: retrospective analysis of previous applications received (Table 1), 15,16,24 RPD survey evaluating the relative importance of candidate characteristics (Table 2), 17,[19][20][21][22][23]25 and contributions of candidate references for interview attainment (Table 3). 13,14,18…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors identified 13 studies meeting inclusion criteria related to the objective of this scoping review (Figure 1) and are described in Tables 1-3. [13][14][15][16][17][18][19][20][21][22][23][24][25] The studies were grouped into three categories: retrospective analysis of previous applications received (Table 1), 15,16,24 RPD survey evaluating the relative importance of candidate characteristics (Table 2), 17,[19][20][21][22][23]25 and contributions of candidate references for interview attainment (Table 3). 13,14,18…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies evaluated the importance of application criteria when selecting an applicant for a residency interview 17,19–23,25 . Four studies collected data via surveys sent to RPDs of ASHP‐accredited residency programs 20–23 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a cross sectional survey of residency directors indicated that “person-organization fit” is desirable when selecting candidates for interviews, meaning that students completing APPEs with characteristics most similar to the residency they are applying for are more likely to receive an invitation to interview. 16 This could also provide an explanation for this result as an ambulatory care clinic within a hospital or large physician group could be perceived as more similar to a hospital residency site.…”
Section: Discussionmentioning
confidence: 96%
“…9 Based on previous studies, pharmacy students appear to perceive clinical rotations timing prior to MCM as very important; on the other hand, residency program directors appeared to consider it as somewhat important, at best, and least influential compared with other APPE characteristics. 15,16 Prior hospital work experience has been associated with a higher likelihood of a student pursuing postgraduate training, but the timing of hospital rotations has not been consistently associated with successful matching. 17,18 Our findings suggest that completion of a hospital rotation prior to MCM is associated with matching.…”
Section: Discussionmentioning
confidence: 99%